Upaya Peningkatan Kualitas Hafalan Al-Qur’an Anak Sekolah Dasar melalui Program Musabaqah Hifzhil Qur’an Berbasis Participatory Action Research (PAR) di Desa Cadassari Purwakarta - Nugraha, Adam Fauzan; N, Narkum; Solehudin, Azis (Yayasan Daarul Huda Kruengmane, 2026)
Cadassari Village, Purwakarta Regency, has strong religious potential as reflected in the activities of Qur’anic Education Centers (TPQ) and community involvement in children’s religious development. Nevertheless, the quality of Qur’an memorization among elementary school children in this village still faces several challenges, particularly in terms of reading fluency, accuracy of verse sequence, and consistency of murojaah (revision). This condition motivated the implementation of a community service program focusing on strengthening the quality of children’s Qur’an memorization through a participatory approach. The program was carried out by actively involving TPQ teachers, parents, and the village community at every stage of the activities using the Participatory Action Research (PAR) approach. Over a five-week implementation period, the activities began with the classification of children’s memorization levels, followed by regular Qur’an murojaah mentoring conducted every evening after the Maghrib prayer, and concluded with the implementation of the Musabaqah Hifzhil Qur’an (MHQ) as an evaluation medium. The MHQ was conducted through verse continuation and the recitation of a selected surah to comprehensively assess the quality of children’s memorization. The implementation of the program demonstrated positive changes in the children’s ability to maintain their memorization, as indicated by improvements in reading fluency, accuracy in verse continuation, and self-confidence when performing in public. In addition to its impact on the development of children’s memorization, the program also increased parental involvement in murojaah mentoring and strengthened the Qur’anic culture within the Cadassari Village community.